Current Situation and Future Prospects of Distance Education for Children with Disabilities in Secondary Schools of Azerbaijan – Challenges and Trends - Nasifov, Tural; Mammadzada, Elyar; Aydamir, Movlud (ADA University, 2018)
Distance education for both secondary and high school students is becoming increasingly common phenomena across the world. Such modern education also considers the people with social needs. Today in the era of developed ICT, digitalization many countries have achieved a lot in the field of providing education to their citizens with special needs. This issue has been in agenda of the relative ministry and agencies in recent years. There are some achievements, and still some deficiencies. The authors of this paper did the research to see the current situation, and to help define possible future proceedings.
Keywords: Distance education -- Azerbaijan.; Inclusive education -- Azerbaijan.; Children with disabilities -- Education.; Public and International Affairs